SIMULATION OF A WELDING ROBOT MANIPULATOR TRAJECTORY IN THE MATLAB/SIMULINK ENVIRONMENT - Sh. S. Djurayev; D. M. Nabijonov; M. M. Abdumajidova (Journals Park Publishing, 2025)
This article presents a methodology developed in the MATLAB/Simulink environment for trajectory planning and simulation aimed at improving the trajectory accuracy of robotic manipulators in industrial welding processes. A control system based on PID control was designed to model and track the movement trajectories of robot manipulators and to develop smooth trajectories and tracking algorithms. The results demonstrate the potential to improve weld quality and increase manufacturing efficiency. Simulation results were analyzed through graphical and tabular representations.
Keywords: Welding robot, trajectory planning, MATLAB/Simulink, PID control, industrial automation.